2016
DOI: 10.1002/jsfa.7589
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a new ribitol dehydrogenase fromProvidencia alcalifaciensRIMD 1656011

Abstract: The substrate specificity indicated that the ribitol dehydrogenase from P. alcalifaciens RIMD 1656011 can be used for direct production of allitol from d-fructose without any by-product formation. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…If polyol dehydrogenase is active on these substrates, D-fructose could be reduced to D-sorbitol or D-mannitol, which would result in impurities in the final product [16]. However, the RDH from P. alcalifaciens that we investigated was not active on D-sorbitol and D-mannitol, which indicated that the enzyme can be used for the production of allitol directly from D-fructose [17]. To the best of our knowledge, there is also an RDH from K. pneumonia which is not active on D-sorbitol and D-mannitol [16].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…If polyol dehydrogenase is active on these substrates, D-fructose could be reduced to D-sorbitol or D-mannitol, which would result in impurities in the final product [16]. However, the RDH from P. alcalifaciens that we investigated was not active on D-sorbitol and D-mannitol, which indicated that the enzyme can be used for the production of allitol directly from D-fructose [17]. To the best of our knowledge, there is also an RDH from K. pneumonia which is not active on D-sorbitol and D-mannitol [16].…”
Section: Discussionmentioning
confidence: 89%
“…D-psicose was previously prepared in our laboratory from Dfructose [19]. Two reconstructed plasmids, containing FDH from the methanol-assimilating yeast O. parapolymorpha DL-1 and RDH from P. alcalifaciens RIMD 1656011 were synthesised by Sangon Biological Engineering Technology and Services (Shanghai, China), in accordance with the protocol reported by Hassanin et al [17].…”
Section: Experimental Chemicals and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…RDHs have been isolated from various sources, such as Aerobacter aerogenes (Fossitt & Wood, 1966), Enterobacter agglomerans (Muniruzzaman et al, 1995b), Gluconobacter oxydans (Adachi et al, 2001), Klebsiella aerogenes (Taylor et al, 1974), Rhodobacter sphaeroides (Kahle et al, 1992), Klebsiella oxytoca (Han et al, 2104), Z. mobilis (Moon et al, 2010), E. aerogenes (Singh et al, 2015) and Providencia alcalifaciens (Hassanin et al, 2015) (Table 2). In addition, RDH catalyses production of D-ribulose from ribitol.…”
Section: Sources Of Rdhsmentioning
confidence: 99%
“…The Michaelis-Menten constants (K m ) of RDHs from K. aerogenes, Rhodobacter sphaeroides, E. agglomerans, G. oxydans, Z. mobilis, E. aerogenes and P. alcalifaciens with ribitol were 8, 6.3, 32.2, 1.2, 11.8, 10.3 and 13.9 mM, respectively (Kahle et al, 1992;Muniruzzaman et al, 1995b;Adachi et al, 2001;Moon et al, 2010;Han et al, 2014;Hassanin et al, 2015;Singh et al, 2015). No previous study has examined the kinetic parameters of reduction in D-psicose into allitol by RDH.…”
Section: Sources Of Rdhsmentioning
confidence: 99%